Bigea: hacia una bibliografía de la gramática escolar argentina - Cordisco, Ariel; De Natale, Carla; Domínguez, Luisa; García Folgado, María José; Gaviño Rodríguez, Victoriano; Indart, Camila; Lidgett, Esteban; Pérez Corti, Sol; Toscano y García, Guillermo (Anales de Lingüística, 2020)
-